Using Graphic Organizers to Improve Paragraph Writing Skills: A Quasi-Experimental Study of English Education Majors - Riyadi, Sugeng (Raden Intan State Islamic University of Lampung, Indonesia, 2025)
This study investigated the effect of using graphic organizers on the paragraph writing skills of English Education majors at UIN Raden Intan Lampung. A quasi-experimental design with a pretest-posttest control group was employed. The participants consisted of two intact classes, with one serving as the experimental group and the other as the control group. The experimental group received writing instruction incorporating graphic organizers, while the control group was taught using conventional methods. Data were collected through paragraph writing tests administered before and after the intervention. Prior to hypothesis testing, normality and homogeneity tests confirmed that the data met the assumptions for parametric analysis. An independent samples t-test revealed a statistically significant difference in post-test scores between the two groups, with the experimental group outperforming the control group. These findings indicate that graphic organizers are effective in enhancing students’ ability to organize ideas, maintain logical flow, and improve overall paragraph quality. The results also demonstrate the potential of graphic organizers as a pedagogical tool to bridge performance gaps among students with varying levels of writing proficiency. This study concludes that integrating graphic organizers into EFL writing instruction can yield substantial benefits, particularly in contexts where learners face difficulties with coherence and idea development.